Prevalence and correlates of loneliness among a nationally representative population-based sample of middle-aged and older adults in India - Pengpid S. (2023)
This study aimed to determine the prevalence and correlates of loneliness in middle-aged and older adults in India. The sample included 72,262 middle-aged and older adults from the cross-sectional 2017-2018 Longitudinal Ageing Study in India (LASI) Wave 1. Loneliness was assessed with a single item. Results indicate that the prevalence of moderate loneliness was 20.5%, and severe loneliness was 13.3%. In adjusted multinominal logistic regression analysis, food insecurity, discrimination experiences, exposure to life event stressors, unsafe home, low life satisfaction, multi-morbidity, functional disability and poor distant vision were positively and being married, high spirituality/religiosity, and medium attendance of religious services, were negatively associated with severe loneliness. In addition, no schooling and poor childhood health were positively associated with moderate loneliness. More than one in ten middle-aged and older adults in India reported severe lone-liness. Several risk and protective factors were identified, which can be targeted in public health interventions.